Characterization of decontamination procedure of beef carcasses at slaughterhouses in the province of Antioquia, Colombia - Sánchez-Acevedo, Mauricio; Peña Serna, Carolina; Garay Pineda, Francisco J.; Silva, Jorge Arturo Fernández (Vitae, 2023)
BACKGROUND: Beef slaughterhouses must use a carcass decontamination procedure to control pathogens and thus prevent foodborne diseases transmitted by meat. OBJECTIVES: This study aimed to characterize beef carcass decontamination procedures at slaughterhouses located in the province of Antioquia (Colombia). All the slaughterhouses were open, registered, and approved by Invima (Instituto Nacional de Vigilancia de Medicamentos y Alimentos in Spanish) at the time of the study. METHODS: This descriptive study collected information from 23 beef slaughterhouses between July 2019 and April 2021 through documentary reviews and visits to slaughterhouses, using forms and questionnaires. RESULTS: The study allowed the characterization of the procedures used to decontaminate beef carcasses, showing that the chemical disinfection of the carcasses is used to control microorganisms in at least 73.9% of the slaughterhouses analyzed. According to secondary sources, it was found that most of the slaughterhouses are small (slaughter volume <50,000 heads per year); 10 of them use citric acid, lactic acid, peracetic acid, and a mixture of organic acids in concentrations between 900 and 1,200 ppm, 1.5 and 1.7%, 180 and 190 ppm, and 900 and 1,200 ppm, respectively, as carcass disinfectants and according to the technical data sheet of the product. During the visits and through the application of the questionnaire, it was found that the 12 slaughterhouses had implemented chemical disinfection which is not scientifically based, using manual devices as an intervention method to control pathogenic microorganisms. It was found that the type of company, slaughter volume, and the lack of financial resources are the determining factors in the selection of decontamination procedures. The validation of the beef carcass decontamination procedures in the different slaughterhouses in the study was demonstrated. CONCLUSIONS:Although it was established that at least one decontamination procedure, such as chemical disinfection, is used in the slaughterhouses of study, this option is not supported by scientific or technical evidence. The findings support the need for improvements in the slaughterhouses of the province of Antioquia, including the improvement of surveillance programs to reduce pathogens in the meat chain effectively.